Multikulturnost in diktatura strpnosti - Rošker, Jana S. (Šolsko polje, 2010)
The article deals with problems related to the concept of tolerance in the context of multicultural interactions. It draws attention to the concrete problems associated with the application of this concept within the framework of basic human rights against the social and political background of traditional and modern China. The author emphasizes the relativity and the cultural conditionality of these supposedly universal values through critical analysis of such examples. Thus, the article shows that the notion of tolerance cannot be separated from the scope of ideological and axiological connotations which are characteristic for Western societies and their ideological apparatuses. Suchlike concepts of tolerance have been advocated by the defenders of pluralism and liberalism. It is therefore of utmost importance in modern globalized societies that are confronted with multicultural issues not to deal with questions of migration, exile or hibridity as though appearing in a simple contradiction to nation, rootedness and authenticity, but to locate and evaluate their ideological, political and emotional links and their cross-sections within multilayered postcolonial histories.
Keywords: postkolonialne študije; multikulturalizem; kritika strpnosti; univerzalnost; človekove pravice; human rights